Are anticonvulsants effective for treating alcohol dependence?. Issue 4 (April 2018) - Duncan, Trisha; Hudson, Jonell; Coulter, Lois; Macechko, Michael
Abstract : EVIDENCE‐BASED ANSWER : Anticonvulsants as a class do not increase abstinence but do decrease heavy drinking and drinks per drinking day by about 1.5 (SOR: A, meta‐analysis of RCTs). Gabapentin (SOR: B, RCT) and topiramate (SOR: C, small RCT) may increase abstinence rates.